The psychological effects of pandemic Covid19: A review of international literature - boussafsaf, zoubir (Journal of Social Sciences and Humanities, 2022)
This article provide an international review of the psychological effects of the COVID19 pandemic on individuals, as well as the effects of prevention measures taken by countries to cope with it, including lockdown and present their results. This review was carried out using Springer, Science direct database and search engine Scholar Google. 16 studies were identified mostly from China based on the predetermined eligibility criteria. An assessment of these studies was performed from criteria predefined by Fink (2014). The results showed different psychological effects of pandemic Covid19 on general population, medical staff and individuals suspected of Covid19.